Pertumbuhan dan Hasil Bawang Merah Pada Berbagai Dosis Trichokompos Kotoran Sapi - Budiyati Ichwan; Irianto Irianto; Eliyanti Eliyanti; Zulkarnain Zulkarnain; Addion Nizoridan; Yogi Ridho Pangestu (Universitas Batanghari, 2022)
Increasing production and productivity of shallots currently must be done by expanding the area of shallot planting. The expansion of shallot planting in Jambi is constrained by Ultisol land which has low soil fertility. This study aims to look at the response of shallots to the application of cow dung trichocompost doses, and to get a dose which will provide the most effective growth and yield of shallots. The research design used was a randomized block design (RBD) with one factor, namely the dose of cow dungtrichocompost consisting of: 0 tonha-1; 7.5 tonha-1; 15 tonha-1; 22.5 tonha-1; and 30 tonha-1. The results showed that the applying of cow dung trichocompost increased plant height, number of leaves, number of bulbs, tuber weight per clove, and bulb weight per clove of shallot. The dose of trichocompost that gave the most effective growth and yield was 22.5 tonha-1, with production 8.5 tonha-1dry bulbs, almost close to BimaBrebes production (9.9 tonha-1 dry bulbs), or 85.8% of the potential yield.Keywords: doses,production, response,Ultisol